Specific Anaerobic Fluidized Bed Bioreactors as Pretreatment to Microfiltration in Domestic Wastewater Treatment for Reuse - Xing, W.; Guo, W. S.; Ngo, H. H.; Listowski, A.; Cullum, P. (Journal of Applied Membrane Science & Technology, 2017)
Practical use of an anaerobic granular activated carbon (GAC) fluidized bed bioreactor (FBBR) as pretreatment to microfiltration was experimentally verified. A nature starch based cationic flocculants (GF) was employed in this study for testifying its impact on the performance of GAC–FBBR. The GAC–FBBR with and without addition of GF was evaluated in terms of dissolved organic carbon (DOC) removal from biologically treated sewage effluent (BTSE). With only a daily addition of 200 mg GF to GAC– FBBR and a depth of GAC of 500 mm, the biomass of GAC increased from 1.5 g/L to 4.2 g/L within operation period of 30 days while the system resulted in 5% better DOC removal. The results indicate that the GAC–FBBR as pretreatment could effectively remove the dissolved organics and improve the critical flux. Compared with the critical flux of BTSE with submerged microfiltration (SMF) alone (20 L/m2.h), the pretreatment by GAC–FBBR successfully increased the critical flux to 30 L/m2.h. Moreover, the addition of GF into GAC–FBBR could help in raising the critical flux to 35 L/m2.h.